Non-structured treatment interruptions (NTIs) among injection drug users in Baltimore, MD - Kavasery, Ravi (2009)
BACKGROUND: We characterized patterns of highly active antiretroviral therapy (HAART) use and predictors of non-structured treatment interruptions (NTIs) among injection drug users (IDUs) in Baltimore, MD. METHODS: 335 IDUs who initiated HAART from 1996-2006 were studied. NTIs were defined as any subsequent six-month interval where HAART was not reported. Predictors of the first NTI and subsequent restart of HAART were examined using Cox regression. RESULTS: 260 (78%) reported ≥1 NTI. Of 215 with ≥1 follow-up visit after the NTI, 44 (20%) never restarted HAART, 62 (29%) restarted and remained on HAART and 109 (51%) reported multiple NTIs. NTIs were less likely among those who initiated HAART in later calendar years and hada recent outpatient visit and more likely among women, persons with detectable HIV RNA at the prior visit and those who reported injecting daily. Among those with NTIs, interuptions occurred earlier in persons who were younger, did not have a prior AIDS diagnosis and were actively injecting; NTIs lasted longer in persons who had higher HIV RNA levels, were incarcerated and drinking alcohol. A recent outpatient visit and not actively injecting were associated with restarting HAART. CONCLUSIONS: NTIs were common in this population and occurred most frequently in the setting of active drug use and disruption of health care. Effective linkages between primary care for HIV and substance abuse treatment may improve HAART outcomes in this population.